Phylogenetic Analysis Reveals Distinct Evolutionary Trajectories of the Fluoroquinolones-Resistant Escherichia coli ST1193 From Fuzhou, China - Huang, Jiangqing; Zhao, Zhichang; Zhang, Qianwen; Zhang, Shengcen; Zhang, Shuyu; Chen, Min; Qiu, Hongqiang; Cao, Yingping; Li, Bin (Frontiers in Microbiology, 2021)
Escherichia coli (E. coli) ST1193 is an emerging fluoroquinolones-resistant and virulent lineage. Large gaps remain in our understanding of the evolutionary processes and differences of this lineage. Therefore, we used 76 E. coli ST1193 genomes to detect strain-level genetic diversity and phylogeny of this lineage globally. All E. coli ST1193 possessed fimH64, filCH5 and fumC14. 94.7% of isolates were classified as O-type O75. 9.33% of E. coli ST1193 possessed K5 capsular, while 90.67% of isolates possessed K1 capsular. The core genome analysis revealed that all isolates were divided into two phylogenetic clades (clade A and B). Clade A included 25 non-Chinese E. coli ST1193 and clade B contained all isolates collected from Fuzhou, China, respectively. The results of comparative genomics indicated Indels were identified in 150 clade-specific genes, which were enriched into the biological process and molecular function. Accessory genome phylogenetic tree showed a high degree of correlation between accessory genome clusters and core genome clades. There was significant difference in antibiotic resistance genes (blaCTX-M-55, blaTEM-1, sul2, tet(B), tet(R), APH(6)-Id and AAC(3)-IId), virulence factors (cia, neuC, gad and tra) and plasmid replicon types (IncQ1, Col156 and IncB/O/K/Z) between clade A (non-Chinese isolates) and clade B (Chinese isolates) (p<0.05). Further analysis of the genetic environments of blaCTX-M-55 demonstrated that the flanking contexts of blaCTX-M-55 were diverse. In conclusion, our results reveal the distinct evolutionary trajectories of the spread of E. coli ST1193 in Fuzhou, China and non-China regions. This supports both global transmission and localized lineage expansion of this lineage following specific introductions into a geographic locality.